ENHANCING KNOWLEDGE OF BULLYING BEHAVIOR THROUGH CREATIVE PEDAGOGY AMONG STUDENTS (Malaysian Journal of Learning and Instruction, 2017)
Purpose â€“ Bullying is one of the most worrying issues among teachers, parents, and students. Hence, prevention action should be taken to prevent bullying at school. Therefore, the Program 2BS: Iâ€™m a Buddy not a Bully, has been implemented with an aim to enhance knowledge on bullying among students. This paper examines the effectiveness of pedagogical creative approaches to increase bullying knowledge and awareness among students. Creative and fun pedagogy have been used as an approach to achieve the objectives of this program.Methodology â€“ A total of 234 students from different school orientations and aged 14â€“16 years participated in this experimental research. This study employs a quantitative method with the support of qualitative approaches utilizing quasi experiments design. An interview was conducted with seven students to obtain a deeper understanding of the effectiveness of creative pedagogy.Findings â€“ The results showed a significant increase in knowledge of bullying behavior among students who had participated in this program. The findings from the interviews show that by using this creative pedagogy approach, students were more excited and could understand the content better.Significance â€“ The findings are significant to teachers and learners, because they can act accordingly towards bullying behavior. This program provides an alternative to implementing bullyingprevention programs that are oriented towards enhancing knowledge on bullying among students.